How to Unleash the Economy of General Intellect to Build a Post-Capitalist World: A review of Kapitalizm sieci [Network Capitalism] by Jan Oleszczuk- Zygmuntowski (Wydawnictwo Rozruch, Warszawa 2020) - Mączyńska, Elżbieta (Journal of Public Governance, 2022)
.